Making matters: craft, ethics, and new materialist rhetorics - Gruwell, Leigh, author; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Writing Studies has become absorbed with new materialist rhetoric, which considers how rhetoric emerges not from independent human agents but instead from complex assemblages of humans and nonhumans. Radical reconfiguration of rhetorical agency raises important questions. This book seeks to answer these questions by situating rhetoric as craft.-- Provided by publisher.
Introduction: rhetoric in the making -- Craft agency: an ethics for new materialist rhetorics -- Crafting history, crafting rhetoric: locating craft agency -- Craftivism and the material specificity of rhetorical action -- Manifesting material relationships online through Ravelry -- The Women's March, digital-material assemblages, and embodied difference -- Rescuing craft for Writing Studies.
Keywords: Rhetoric -- Social aspects; Rhetoric -- Moral and ethical aspects; Materialism -- Moral and ethical aspects; Online social networks -- Political aspects; Craftivism; Feminism and rhetoric